Illness perceptions in adolescents with chronic fatigue syndrome and other physical health conditions: Application of the common sense model. (July 2019) - Haines, Cara; Loades, Maria; Davis, Cara
Background: The common sense model (CSM) proposes that illness perceptions guide coping and illness management, which subsequently affects outcomes. Chronic fatigue syndrome (CFS) is associated with severe functional impairment. CFS is distinct from other physical health conditions in that individuals can experience high levels of uncertainty, stigma and disbelief from others. This study aimed to compare illness perceptions in adolescents with CFS with other physical health conditions, using a cross-sectional, between-groups design. Methods: Adolescents (aged 11–18) with CFS ( n  = 49), type 1 diabetes ( n  = 52) and juvenile idiopathic arthritis ( n  = 42) were recruited through National Health Service (NHS) clinics and online, and completed a series of questionnaires. Results: Adolescents with CFS differed on the perceived consequences, timeline, personal control, treatment control, identity and understanding dimensions of illness perceptions. Except for identity, these dimensions were predicted by health condition even when accounting for age, gender, fatigue, physical functioning, anxiety and depression. Conclusions: Results offer preliminary evidence for the applicability of the CSM in adolescents, with implications for supporting adolescents with physical health conditions. Results suggest that psychological interventions targeting perceived control, understanding and identity may have particular utility for adolescents with CFS.